2000
DOI: 10.1128/jb.182.7.1949-1955.2000
|View full text |Cite
|
Sign up to set email alerts
|

A 90-Kilobase Conjugative Chromosomal Element Coding for Biphenyl and Salicylate Catabolism in Pseudomonas putida KF715

Abstract: The biphenyl and salicylate metabolic pathways in Pseudomonas putida KF715 are chromosomally encoded. The bph gene cluster coding for the conversion of biphenyl to benzoic acid and the sal gene cluster coding for the salicylate meta-pathway were obtained from the KF715 genomic cosmid libraries. These two gene clusters were separated by 10-kb DNA and were highly prone to deletion when KF715 was grown in nutrient medium. Two types of deletions took place at the region including only the bph genes (ca. 40 kb) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 40 publications
1
51
0
1
Order By: Relevance
“…It was reported that the bph gene cluster involved in the metabolism of biphenyl/4-chlorobiphenyl is located in the 55-kb transposon Tn4371 (17,18,33,34). Our recent study also revealed that the 90-kb bph-sal element coding for biphenyl and salicylate metabolism behaves like a conjugative transposon in Pseudomonas putida KF715 whose bph gene cluster is nearly identical to that of KF707 except that the bphX0X1X2X3 genes were deleted (35). If this is the case in KF707, the bph genes could be foreign genes derived from other strains.…”
Section: Discussionmentioning
confidence: 81%
“…It was reported that the bph gene cluster involved in the metabolism of biphenyl/4-chlorobiphenyl is located in the 55-kb transposon Tn4371 (17,18,33,34). Our recent study also revealed that the 90-kb bph-sal element coding for biphenyl and salicylate metabolism behaves like a conjugative transposon in Pseudomonas putida KF715 whose bph gene cluster is nearly identical to that of KF707 except that the bphX0X1X2X3 genes were deleted (35). If this is the case in KF707, the bph genes could be foreign genes derived from other strains.…”
Section: Discussionmentioning
confidence: 81%
“…They can excise and transfer to recipients through conjugation (mating) and integrate into the chromosome of the recipient (5,6). ICEs encode proteins required for conjugal transfer and can also encode proteins involved in resistance to antibiotics (5,6), metabolism of alternative carbon sources (4,8), symbiosis (9), and other processes (10). ICEs and putative ICEs have been found in many bacteria (10) and are important agents of horizontal gene transfer because they are capable of moving themselves and other DNA to recipients (6,(11)(12)(13).…”
mentioning
confidence: 99%
“…A 90-kb DNA region including both the bph and sal genes (termed bph-sal element) was transferred by conjugation from KF715 to P. putida AC30 (Nishi et al, 2000). These transconjugants gained the ability to grow on biphenyl and salicylate as sole sources of carbon.…”
Section: The Bph Genes As Conjugative Elementsmentioning
confidence: 99%
“…KKS102 are shuffled, and the bphA4 gene is downstream of bphD (Kikuchi et al, 1994a, b). The bph cluster in Pseudomonas putida KF715 is lacking the 3.5 kb bphX region (Hayase et al, 1990;Nishi et al, 2000). In the Rhodococcus sp.…”
Section: Pcb Catabolic Genesmentioning
confidence: 99%
See 1 more Smart Citation